A Analisis Perlindungan Konsumen dalam Tindakan Penyalahgunaan Data Pribadi oleh Penyelenggara Pinjaman Online Berdasarkan Perspektif Hukum Indonesia - Novri, Novrianti; Amboro, Florianus Yudhi Priyo; Hutauruk, Rufinus Hotmaulana (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The emergence of regulations regarding personal data in 2022 is eagerly awaited and anticipated by consumers who feel aggrieved by online service managers, especially in the field of online-based loan financial services. The rules that specifically regulate the protection of personal data are Law no. 27 of 2022 concerning Personal Data Protection, prior to the existence of special regulations regarding personal data, the ITE Law and other similar legal regulations were used as a reference for consumer protection. Law Number 27 of 2022 concerning Personal Data Protection was formed so that it does not overlap with other regulations that guarantee the protection of personal data in the community. In addition to these regulations, there are still several regulations governing this matter, namely Law Number 11 of 2016 on amendments to Law Number 11 of 2008 concerning ITE, provisions of the Financial Services Authority (OJK) Number 1/POJK.07/2013 concerning Consumer Protection and OJK Provisions Number 77/POJK.01/2016 concerning Online-Based Loan Services. The research method used to write this article is a normative research method which is defined as research that has basic material from data in similar journals, articles, theses, theses, and so on. Consumers who are harmed can act legally with two choices, namely arbitration and litigation channels, if arbitration has been carried out then there is no agreement between the two parties for peace then they can pursue litigation channels by reporting this matter to the local police or can file lawsuits against the law to local District Court.